Seismic monitoring of carbonate reservoirs using stochastic time-lapse inversion - Góes Castro Meira, Mateus (Curtin University, 2016)
I investigate the capability of stochastic inversion to estimate dynamic reservoir properties and their uncertainty from time-lapse seismic data. To this end, I develop a multidisciplinary stochastic inversion workflow and test its performance on a synthetic dataset based on flow simulations from an Australian CO2 geosequestration project. Application of this workflow to a field dataset over a producing carbonate reservoir offshore Brazil gives dynamic properties estimates consistent with the flow simulation results.